Affective factors that influence in english oral production in the 8th level egb students of the educational unit “Yahuarcocha”, Ibarra canton, school year 2018-2019 - Quishpe Toapanta, Diana Karina (2019)
Apply methodological strategies to minimize the effects of anxiety and enhance the student’s self-esteem on the oral production of the foreign language.